HAZARDOUS AND TOXIC WASTE (HTW) MANAGEMENT LIABILITY IN THE PERSPECTIVE OF CIVIL LAW - Prasetyo, Dr. Dossy Iskandar; Puspitasari, Enggar (jfpublisher, 2024)
A person or legal entity can assume responsibility for hazardous and toxic waste (HTW) management. The Environmental Protection and Management Law (UUPLH) aims to protect the environment from pollution, including HTW. This waste is generated from industrial or human activities that pose a great potential for environmental damage and threats to the lives of the living. Therefore, HTW should be managed properly to prevent pollution that endangers the ecosystem. Business actors or communities that are unable to manage HTW independently can seek the assistance of third parties who have expertise in the management of such waste. This collaboration is necessary to assure that HTW is managed effectively, in accordance with applicable regulations, thus avoiding additional risks to the environment and public health. This research aims to increase awareness of the importance of HTW management and the inherent responsibilities of the parties involved. This research adopts a normative juridical approach, which refers to regulations, legal concepts, and relevant literature studies. Drawing on secondary data obtained from relevant literature and regulations related to HTW, this research highlights the importance of HTW management in preventing threats to the environment and ensuring the sustainability of the living environment. The findings of this research suggest that proper HTW management is key to protecting the environment from the dangers of pollution and supporting the sustainability of ecosystems and human welfare in the future.